Comparison of anterior knee laxity immediately after anatomic double-bundle anterior cruciate ligament reconstruction: Manual tensioning vs tensioning boot techniques - Tatsuo Mae; Yukiyoshi Toritsuka; Hiroyuki Nakamura; Ryohei Uchida; Shigeto Nakagawa; Konsei Shino (Elsevier, 2022)
Purpose: Tensioning technique at graft fixation is one of key factors for successful outcomes in ACL reconstruction. The tensioning boot, which had two tensioners and was fixed to the tibia with a bandage, was developed for precise graft tensioning. The purpose was to compare the anterior knee laxity between the manual tensioning and the tensioning boot techniques immediately after ACL reconstruction under anesthesia in order to elucidate the effectiveness of using the tensioning boot. Methods: 33 patients had anatomic double-bundle ACL reconstruction with semitendinosus tendon graft. After grafts were fixed with EndoButton-CL on lateral femoral cortex, grafts were tied to Double Spike Plate (DSP). Each graft was pre-tensioning with 20 N (totally 40 N) at 20 degree of flexion for 3 minutes using manually-held tensioner in 11 patients and using tensioner installed to tensioning boot in the remaining 22 patients before graft fixation, and were then fixed in the same manner. Tibial displacement under 67 and 89 N of tibial anterior load was measured by KT-2000 Knee Arthrometer under anesthesia before and immediately after operation. Results: The anterior knee laxity in the operated knee was 4.5 ± 1.0 mm in the manual tensioning group and 2.9 ± 0.9 mm in the tensioning boot group at 89 N of anterior load, showing a significant difference. (P < .0001) The side-to-side difference in the manual tensioning group was significantly less than that in the tensioning boot group. (P = .002) Conclusions: Anterior laxity of the operated knees as well as KT side-to-side difference immediately after ACL reconstruction was larger in the tensioning boot technique than the manual tensioning technique, when the graft was fixed in the same manner. Thus, the initial tension at graft fixation with the tensioning boot can be smaller than 40 N.